The effect of dietary sericite on growth performance, digestive enzymes activity, gut microbiota and haematological parameters of Nile tilapia, Oreochromis niloticus (L.) fingerlings - Hassaan, Mohamed S. (2021)
A feeding trial was conducted to assess the effect of dietary supplementation of sericite (silicate clay) on growth performance, digestive enzymes activity, immune parameters and gut microbiota, of Nile tilapia, Oreochromis niloticus (L.) fingerlings. Five isonitrogenous diets were formulated each diet supplemented with different levels of sericite 0 (control), 2.5, 5, 7.5 and 10 g/kg diet. After 70 days of feeding trial, supplemental sericite were quadratically improved the final body weight (FBW) (P = 0.023), weight gain (WG) (P = 0.012), specific growth rate (SGR) (P = 0.023) and feed conversion ratio (FCR) P = 0.023) and protein efficiency ratio (PER) (quadratic, P = 0.045). However, the relationship between FCR and sericite levels was expressed by a broken-line model with an identified optimal breakpoint of 6.3 g/kg of sericite inclusion in the diets. Additionally, significant quadratic increase in alkaline phosphatase (ALP), amylase, trypsin, chymotrypsin and lipase enzymes were detected (P = 0.026; P = 0.023; P = 0.013; P = 0.045; P = 0.023) as the level of sericite increased in the diet. Furthermore, dietary sericite levels exhibited linear decreased in the total count bacteria, E. coli and Enterobacteriaceae of stomach and gut of experimental fish (linear, P = 0.032; P = 0.024; P = 0.035; P = 0.023; P = 0.012; P = 0.039, respectively). There was no effect of dietary sericite levels on hemoglobin (Hb), hematocrit (Htc) and red blood cells (RBCs), but a quadratic trend was observed in white blood cells (WBCs), monocytes and lymphocytes of fish (quadratic, P = 0.036; P = 0.013; P = 0.034), respectively. Increasing dietary sericite levels did not affect alanine aminotransferase (ALT), aspartate aminotransferase (AST), albumin and globulin but quadratically increased total protein (quadratic, P = 0.012) and IgM exhibited linear trend (linear, P = 0.045). Results in this study indicate that the addition of sericite as feed additive enhanced the growth, feed utilization, digestive enzyme activities, blood profile and gut biota of Nile tilapia.